Co-Benefits of REDD+ in Community Managed Forests in Nepal - Joshi, Laxman; Karky, Bhaskar Singh; Poudel, Krishna Chandra; Bhattarai, Keshav; Dangi, Resham; Acharya, Krishna; Uprety, Batu; Singh, Vijay; Chand, Narendra; Manandhar, Ugan (Journal of Forest and Livelihood, 2013)
DOI: http://dx.doi.org/10.3126/jfl.v11i2.8623 Journal of Forestry and Livelihood Vol.11(2) 2013 65-68